The sociocultural context of pediatric pain: an examination of the portrayal of pain in children's popular media. Issue 3 (March 2021) - Mueri, Kendra; Kennedy, Madison; Pavlova, Maria; Jordan, Abbie; Lund, Tatiana; Neville, Alexandra; Belton, Joletta; Noel, Melanie
Abstract : Abstract: Pain (eg, needle injections, injuries, and chronic pain) is highly prevalent in childhood and occurs in social contexts. Nevertheless, broader sociocultural influences on pediatric pain, such as popular media, have not been empirically examined. This study examined how pain is portrayed and gendered in children's popular media. A cross-section of children's media targeted towards 4- to 6-year-old children was selected based on popularity, including 10 movies and the first season of 6 television shows. Pain instances were extracted and coded using 2 established observational coding systems assessing sufferer pain characteristics and observer responses (eg, empathic responses). Findings identified 454 instances of pain across the selected media. Violent pain (ie, intentionally inflicted) and injuries were most commonly represented, whereas everyday, chronic-type, and procedural pains were infrequently portrayed. Pain instances were more commonly experienced by boy characters, who also expressed greater distress; yet, observers were more responsive (eg, expressed greater concern) towards girl characters' pain. Overall, observer responses to pain were infrequent, with observers witnessing but not responding to nearly half of pain instances. Observers who did respond expressed an overall lack of empathy towards sufferers. These findings reveal a very narrow depiction of pain presented in children's popular media, with an overall underrepresentation of pain, numerous maladaptive portrayals of pain, and gender differences in both sufferer and observer responses. This study underscores the need for further research to inform how children's popular media is perceived by parents and children and how media may be transformed and harnessed for effective pain education in childhood. Abstract : A narrow depiction of pain was presented in children's popular media, with an overall underrepresentation of pain, numerous maladaptive portrayals of pain, and gender differences in both sufferer and observer responses.